Perhitungan HPP Secara Praktis dan Akurat dengan Excel: Solusi Bagi Pengusaha Dapur Tahu - Rivandi, Muhammad; Ananda, Febryandhie; Meirina, Elsa; Umar, Desyani; Putra, Gerry Hamdani (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Calculating the Cost of Goods Production (COGS) is an important aspect in managing a business, especially for entrepreneurs in the culinary sector, such as tofu kitchen entrepreneurs. Accurate and practical COGS will determine success in determining selling prices and maximizing profits. In this dedication, practical and accurate HPP calculation solutions using Microsoft Excel are discussed. Using Excel as a tool allows entrepreneurs to manage data on raw materials, labor costs and overhead costs in a more structured manner. By applying customized formulas and Excel features, kitchen entrepreneurs can calculate COGS quickly, minimize calculation errors, and produce transparent reports. The implementation method is by providing presentation material to Tofu Factory employees. This solution is expected to provide time efficiency and increase profitability for tofu kitchen entrepreneurs in facing the challenges of market competition. The results obtained provide useful knowledge for tofu factory owners and employees who can understand the application of using Excel in determining HPP practically and simply.